Contrasts in kinship structure in mammalian societies. (6th May 2020) - Dyble, Mark; Clutton-Brock, Tim H
Abstract: Comparative studies of mammals confirm Hamilton's prediction that differences in cooperative and competitive behavior across species will be related to contrasts in kinship between group members. Although theoretical models have explored the factors affecting kinship within social groups, few have analyzed the causes of contrasts in kinship among related species. Here, we describe interspecific differences in average kinship between group members among social mammals and show that a simple mathematical model that includes the number of breeding females, male reproductive skew, and litter size successfully predicts 95% of observed variation in average kinship between group members across a sample of mammals. Our model shows that a wide range of conditions can generate groups with low average relatedness but only a small and rather specific set of conditions are likely to generate high average levels of relatedness between their members, providing insight into the relative rarity of advanced forms of cooperation in mammalian societies. Abstract : Cooperative behavior in mammals is most often seen in species that live in groups of closely related individuals. It is, therefore, important to establish how and why the kinship structure of mammal groups varies between species. Using mathematical modeling, we show that these differences are a consequence of differences in litter size, dispersal, reproductive skew, and the number of breeding adults of each sex.